Racionalidade em organizações não governamentais na Paraíba - Mendonça Junior, Izaias Carlos de (2017)
This research aimed to analyze the rationality of non-governmental organizations in the state of Paraiba, Brazil. Three organizations were surveyed in different mesoregions of the state acting in the field of Education. We traced the theoretical, conceptual and historical aspects of the NGOs and followed the theoretical paths of rationality through authors such as Polanyi (2000) and Weber (1999), in the genesis of this discussion. However, it is in Guerreiro Ramos that this discussion is configured as organizational. Following some authors who continued the initial path of Guerreiro Ramos (1981), we came to Rationalities Analysis of Serva (1996) and discussed about authors who have used this method in their research. To enter the field of study, we used the qualitative method. The main resource used for data collection was the semi-structured interview, supplemented with the unstructured observation and analysis of documents. The analysis method followed the content analysis framework. We interviewed 18 people - six from each NGO. The interviewed sample was divided into two paid workers, two volunteers and two managers (paid or volunteer). The result of this work demonstrated that, in the studied NGOs, substantive rationality prevails with a high intensity in two organizations, and a very high intensity, in the other. Considerations were made showing the relationships between the historical and conceptual nature of NGOs, including those of Education, and substantive rationality. We also noted possible influences on organization Rationality from interinstitutional relationships and the context which they are inserted.